1965
DOI: 10.1121/1.1909629
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Evidence for the Stevens Power Function in Man

Abstract: Human evoked cortical responses to acoustic stimuli occurring within 150-170 msec after stimulus onset yielded input-output functions fairly comparable with Stevens' power functions from psychophysical experiments. The objective threshold and equal-loudness contours thus obtained were both in fair agreementwith the well-known subjective measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(32 citation statements)
references
References 0 publications
2
29
0
1
Order By: Relevance
“…For all BER components, however, the exponents were smaller than the value obtained for the intensityloudness function. This finding is consistent with similar comparisons for exponents of intensity functions of late and midlatency evoked potential components (Botte, Bujas, & Chocolle, 1975;Davis & Zerlin, 1966;Keidel & Spreng, 1965;Madell & Goldstein, 1972;Walsh, 1979).…”
Section: Data Reductionsupporting
confidence: 79%
See 1 more Smart Citation
“…For all BER components, however, the exponents were smaller than the value obtained for the intensityloudness function. This finding is consistent with similar comparisons for exponents of intensity functions of late and midlatency evoked potential components (Botte, Bujas, & Chocolle, 1975;Davis & Zerlin, 1966;Keidel & Spreng, 1965;Madell & Goldstein, 1972;Walsh, 1979).…”
Section: Data Reductionsupporting
confidence: 79%
“…The successful application of the power law to psychophysical functions has encouraged speculation on the question of whether changes in evoked potential activity which are contingent on changes in stimulus intensity can be described by power functions with exponents similar to those obtained in psychophysical studies (S. S. Stevens, 1970Stevens, , 1971. Within the auditory modality, there is some evidence to suggest that the growth in amplitude of the late msec) components of the auditory averaged evoked response with increases in stimulus intensity can be adequately described by power functions (Botte, Bujas, & Chocolle, 1975;Davis, Bowers, & Hirsh, 1967;Davis & Zerlin, 1966;Keidel & Spreng, 1965; Walsh, 1979). Power functions have also been derived for the midlatency (15-80 msec) components (Madell & Goldstein, 1972).…”
mentioning
confidence: 80%
“…This wave (latency, 100-170 msec) most likely corresponds to the prominant N1 component of the auditory vertex potential , which has been related to stimulus intensity (Rapin, Schimmel, Tourk, Krasnegor, & Pollak, 1966) and to psychophysical judgments of loudness (Keidel & Spreng, 1965;Davis & lerlin, 1966;Davis, Bowers, & Hirsh, 1968). Tanis (1972) has recently reported that the amplitude of the N1-P2 complex was correlated with psychophysical judgments in an auditory intensity discrimination task (4 vs 5.8 dB HL).…”
mentioning
confidence: 99%
“…It is now well established that the amplitude of the evoked brain response (EBR) is related to changes in auditory (Davis & Zerlin, 1966;Keidel & Spreng, 1965;Schweitzer, 1977;Tepas, Boxerman, & Anch, 1972) and visual (Dinges & Tepas, 1976;Kress, 1975;Shipley, Jones, Wayne, & Fry, 1966;Tepas, Guiteras, & Klingaman, 1974) stimulus intensity. Although these relationships are most frequently linear, their exact form is not clear.…”
mentioning
confidence: 99%